Factor the equation so...
(r^2-pr) and (p^2q-pqr)
Factor out (r^2-pr) = r(r-p)
Factor out (p^2q-pqr) = pq(p-r)
Add a negative to r(r-p) to make it -r(p-r)
(pq-r)(p-r) is the answer... I'm sorry I can't explain things well, but I tried.
Answer:
w=-7/2z
Step-by-step explanation:
to solve for w you firstly have to group the like terms
5w-3w=2z-9z
2w=-7z
then you have to divide both sides by 2 inorder to remain with w on one side.
2w/2=-7/2
w=-7/2
I hope this helps
Answer:
Step-by-step explanation:
given,
a) √x + 6 = 4
to solve the above equation subtract both side with 6
√x + 6 - 6 = 4 - 6
√x = -2
squaring both side
(√x)² = (-2)²
x = 4
a) ∛x + 6 = 4
to solve the above equation subtract both side with 6
∛x + 6 - 6 = 4 - 6
∛x = -2
cubing both side
(√x)³ = (-2)³
x = -8
The equation in slope intercept form would be: y= 1/26x - 2